Nuisance, trash, tool, and treasure? A closer look at the cultural interpretation and uses of household solid waste: implications on waste management - Fakunle, Sunday Olutayo (Frontiers in Sustainability, 2025)
Studies have delved into household members' perceptions toward the generation of household solid waste (HSW). However, there remains a crucial gap in the literature regarding the cultural interpretation of waste as an underlying factor influencing these perceptions. Based on the premise that people's culture influences their activities, one of the practical ways to understand the factors that shape people's relationship with their HSW is to uncover the hidden complex web of cultural interpretations, beliefs, and values. Therefore, this exploratory study sought to investigate people's subjective cultural interpretations of the interplay between their way of life and household solid waste (HSW) generation. The purposive sampling method was utilized to select three indigenous quarters, namely Iremo, Ilode, and Ilare, in Ile-Ife, the cradle of Yoruba culture and civilization. From each of the selected quarters, a convenience sampling method was utilized to select 10 participants. Therefore, an aggregate of 30 participants formed the sample size for the face-to-face in-depth interview as the data collection method. Thematic and content analyses were adopted for the data analysis. The study found that there were several cultural interpretations of HSW among the Yoruba residents of Ile-Ife. These interpretations ranged from viewing the waste as a symbol of affluence, poverty, and social status; a symbol of culture lag; a tool to indicate disobedience and to inflict on other people; a tool for sanction; and as among the materials to build spirits' abodes. The study concluded that culture (beliefs, norms, values, customs, and symbols) had influenced HSW generation in the study location with the implication that the diversity of cultural interpretations and meanings attached to HSW necessitates a culturally sensitive approach to solid waste management.